Uganda : First Review Under the Policy Support Instrument and Modifications to Assessment Criteria; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uganda. (IMF Staff Country Reports; Country Report, 2007)
The staff report for the First Review under the Policy Support Instrument and Modifications to Assessment Criteria discusses Uganda's medium-term expenditure framework (MTEF). The MTEF aims at higher public savings based on spending restraint and a rising domestic revenue ratio. The Bank of Uganda (BOU) will rely on a combination of foreign exchange sales and open market operations to sterilize liquidity. Better and more extensive transport networks and expansion of the pool of long-term savings are also critical for sustainable economic growth.